2022
DOI: 10.3390/coatings12040446
|View full text |Cite
|
Sign up to set email alerts
|

Wear Study of a Magnetron-Sputtered TiC/a-C Nanocomposite Coating under Media-Lubricated Oscillating Sliding Conditions

Abstract: Friction and wear performance of non-reactively magnetron-sputtered hydrogen-free TiC/a-C coatings were characterized under lubricated oscillating sliding conditions against 100Cr6 steel. The friction mediators, isooctane, ethanol and distilled water, were chosen to address the actual trend of environmentally friendly green technologies in mobility and the potential use of carbon-based nanocomposite thin film materials for tribocomponents in contact with gasoline and alternative biofuels. Sliding pairs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Recently, many studies have revealed that incorporating silicon elements into DLC films can enhance their frictional characteristics in a water environment. Some argued that the lower friction coefficient of Si-DLC films, in comparison to DLC films, can mainly be attributed to the colloidal silica produced due to chemical reactions initiated by friction at the sliding interface. For instance, Oguri et al pointed out that the Si-DLC film exhibits superior low-friction properties when compared to the DLC film. This phenomenon is ascribed to the formation of a silicon sol at the friction interface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have revealed that incorporating silicon elements into DLC films can enhance their frictional characteristics in a water environment. Some argued that the lower friction coefficient of Si-DLC films, in comparison to DLC films, can mainly be attributed to the colloidal silica produced due to chemical reactions initiated by friction at the sliding interface. For instance, Oguri et al pointed out that the Si-DLC film exhibits superior low-friction properties when compared to the DLC film. This phenomenon is ascribed to the formation of a silicon sol at the friction interface.…”
Section: Introductionmentioning
confidence: 99%
“…With the popularization of DLC coatings, silicon (Si) diamond-like films (Si-DLC) have been found to have higher hardness, smaller friction coefficient, higher wear resistance and better thermal stability performance [5][6][7]. The microstructure of Si-DLC films prepared by different methods and processes have great differences, which can affect various properties of Si-DLC films, giving theoretical and technical possibilities for the property adjustment of Si-DLC films.…”
Section: Introductionmentioning
confidence: 99%